Satisfaction with teaching and learning quality among undergraduate pharmacy students in a Nigerian university - Onah, Paul Otor; Abdulateef, Siyaka; Abdulmalik, Ahmed (International Journal of Research in Medical Sciences, 2021)
Background: There is increasing acceptance that learning environment has significant impact on academic performance. Learning and teaching experiences influence satisfaction and perception of quality. Pharmacy education in Nigeria is evolving rapidly with new emphasis on acquisition of cognitive skills that upon graduation students can effectively implement pharmaceutical care. The evaluation of satisfaction can be used as a measure of quality and feedback system of teaching and learning experiences of students. The purpose of this study is to assess satisfaction with teaching and learning and their determinants. Methods: This was a cross sectional survey study involving third to fifth year pharmacy students. The educational service quality instrument was used to elicit response on items related to satisfaction. The 37-item questionnaire was administered on consenting students to elicit responses on a five-point Likert scale. The data was analyzed using descriptive statistics and one way ANOVA with post Hoc test. Factor analysis using principal component analysis and varimax rotation was used to identify items that have the most impact on satisfaction. P≤0.05 was considered statistically significant Results: Majority of students have less than average satisfaction across six domains of the instrument, though significant differences exist between lower and higher-level students in areas of administration and expertise (p<0.01). Several studies reported contrasting results some of which have comparable results with this study. Satisfaction and its determinants vary widely so emphasis should be in areas that produce the greatest impact on academic performance Conclusions: Satisfaction with quality of learning is generally low and there is need for institutions leadership to improve learning environment for students.